Prognostic value of PCSK9 Levels in Non-ST elevation myocardial infarction patients undergoing percutaneous coronary intervention. (14th October 2021) - Wang, J.-X; Han, P; Gao, M.-D; Xiao, J.-Y; Li, X.-W; Zhang, N; Ma, J; Cui, Z; Yao, T.-T; Chen, Y; Gao, J; Liu, Y
Abstract: Background: The role of proprotein convertase subtilisin/kexin type 9 (PCSK9) in predicting major adverse cardiovascular events (MACEs) in Non-ST elevation myocardial infarction (NSTEMI) patients is still an open question and the PCSK9 concentration of clinical usefulness remains unknown in guiding treatment. Purpose: To explore the role of PCSK9 in predicting major adverse cardiovascular events (MACEs) in Non-ST elevation myocardial infarction patients. Methods: 272 patients with NSTEMI were included in our study, all patients received PCI therapy after admission. Patients were followed up for 1 year and MACEs were recored. Their baseline plasma PCSK9 levels were determined by ELISA. Patients were divided into high, medium and low PCSK9 groups and the associations of PCSK9 with other biomarkers and MACEs were evaluated. Results: The results showed that PCSK9 levels was related to levels of lipoproteins, high-sensitivity C-reactive protein (r=0.162, P=0.008), platelet volume distribution width (r=0.299, P<0.001) and D-dimer (r=0.285, P<0.001). And the concentrations of PCSK9 was greater higher in people with MACEs (137.2ng/ml vs 243.6ng/ml) (Fig. 1A). The Kaplan-Meier curves showed patients with high PCSK9 level had lower event-free survival rate (Fig. 1B). Survival analysis indicated high level of PCSK9 predicted MACEs independently after adjusted for traditional cardiovascular risk factors and GRACE score (HR=2.646, 95CI%: 1.047–6.686, P=0.027) (Fig. 1C, Fig. 2). Subgroup analysis demonstrated the prognostic value of high PCSK9 level was greater for patients classified by the GRACE score as high risk (Fig. 1D). Conclusions: In a NSTEMI setting, the concentration of PCSK9 is associated with hypercoagulability and hyper-inflammation. High levels of PCSK9 independently predict future MACEs in NSTEMI patients, particularly those classified by the GRACE score as high risk. FUNDunding Acknowledgement: Type of funding sources: None.